Behavior-Based Pricing: An Analysis of the Impact of Peer-Induced Fairness - Li, Krista J.; Jain, Sanjay (Management Science, 2016)
Firms tracking consumer purchase information often use behavior-based pricing (BBP), i.e., price discriminate between consumers based on preferences revealed from purchase histories. However, behavioral research has shown that such pricing practices can lead to perceptions of unfairness when consumers are charged a higher price than other consumers for the same product. This paper studies the impact of consumers’ fairness concerns on firms’ behavior-based pricing strategy, profits, consumer surplus, and social welfare. Prior research shows that BBP often yields lower profits than profits without customer recognition or behavior-based price discrimination. By contrast, we find that firms’ profits from conducting BBP increase with consumers’ fairness concerns. When fairness concerns are sufficiently strong, practicing BBP is more profitable than without customer recognition. However, consumers’ fairness concerns decrease consumer surplus. In addition, when consumers’ fairness concerns are sufficiently strong, they reduce inefficient switching and improve social welfare. This paper was accepted by J. Miguel Villas-Boas, marketing.